2009
DOI: 10.17221/26/2009-pps
|View full text |Cite
|
Sign up to set email alerts
|

The viral etiology of tomato yellow leaf curl disease - a review

Abstract: Glick E., Levy Y., Gafni Y. (2009): The viral etiology of tomato yellow leaf curl disease -a review. Plant Protect. Sci., 45: 81-97.Tomato yellow leaf curl disease (TYLCD) is one of the most devastating plant diseases in the world. As a result of its continuing rapid spread, it now afflicts more than 30 tomato growing countries in the Mediterranean basin, southern Asia, Africa, and South, Central and North America. The disease is caused by a group of viral species of the genus Begomovirus, family Geminiviridae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 119 publications
(88 reference statements)
1
44
0
Order By: Relevance
“…The respondents reported that the disease can cause yield losses ranging from less than 10% to over 40% (Table 4). This result corroborates the report of Glick et al (2009) which states that TYLCV is so destructive that it can cause a yield loss as high as 100%. …”
Section: 3supporting
confidence: 92%
“…The respondents reported that the disease can cause yield losses ranging from less than 10% to over 40% (Table 4). This result corroborates the report of Glick et al (2009) which states that TYLCV is so destructive that it can cause a yield loss as high as 100%. …”
Section: 3supporting
confidence: 92%
“…Outbreaks of TYLCV in India, a country whose farming infrastructure is similar to that of China, cause yield losses ranging from 50-100% (Reddy et al 2010). By way of comparison, TYLCV outbreaks in the early 2000s that reduced tomato yields by 20% in North America and Europe had a cost of more than US$300 million (Glick et al 2009). Given the polyphagous nature of Bemisia tabaci, the hundreds of viruses it can vector, and the extensive agricultural sector in China, the total economic cost of TYLCV and other viral pathogens are likely higher, perhaps dramatically so.…”
Section: Discussionmentioning
confidence: 99%
“…Tomatoes contribute to a healthy diet by providing rich amount of minerals, essential amino acids, sugars and dietary fibers etc. It comprises of abundant vitamin B, C, iron and phosphorus (Glick et al, 2009).…”
Section: Introductionmentioning
confidence: 99%